ANTIOXIDANT ACTIVITY AND CYTOTOXIC POTENTIAL OFHYDROALCOHOLIC EXTRACT OF SALACIA FRUTICOSA (ROOT)-IN VITRO - K, Manjuladevi.; Dhanalakshmi, M.; Thenmozhi, S.; S, Sarumathy.; Ravichandran, V. (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: To evaluate the antioxidant and cytotoxic potential of hydroalcoholic extract of Salacia fruticosa Heyne ex Lawson-root by various In-Vitro methods. Methods: The various concentration of hydroalcoholic extract was evaluated for antioxidant activity and cytotoxic potential using standard methods like ABTS, hydroxyl, DPPH, nitric oxide radical scavenging activity, reducing power assay and MTT assay respectively. Results: Antioxidant activity showed that the IC50 values of extract was found to be 13.62 Î¼g/ml, 134.64Î¼g/ml, 35.53 Î¼g/ml & 66.23 Î¼g/ml in ABTS, hydroxyl, DPPH & nitric oxide radical scavenging activity respectively and reducing power gets increased with increasing the concentration of extract which was compared with the standards ascorbic acid and rutin. The cytotoxic potential showed that the IC50 values of extract was found to be 129.13 Î¼l/ml, 151.33 Î¼l/ml, 203.25 Î¼l/ml and 302.33 Î¼l/ml for Human Colon Cancer Cells (HT-29), Human Liver Cancer Cells (HepG2), Human Breast Cancer Cells (MCF-7) and Normal Human Dermal Fibroblast (NHDF) respectively. The extract showed dose dependent inhibition of viable cells & produced potent proliferative inhibitory action on cancer cell lines. The relative sequence of sensitivity to extract was observed to be HT-29>HepG2>MCF-7>NDHF cell lines. Conclusion: Thus our results conclude that the hydroalcoholic extract of Salacia fruticosa-root was found to be potent antioxidant & anticancer agent. Further studies are undergoing in order to clarify their molecular mechanisms by isolating the active principle present in the root. Â